DESAIN KEMASAN BAHAN DAPUR BERBENTUK SERBUK DENGAN MENGGUNAKAN PENDEKATAN KANSEI ENGINEERING - Alifta Dicasani; Hari Purnomo (Teknoin, 2016)
Herbs widely circulated in the powder form wrapped in packaging with certain dose. To make it easier to measure the dose, it needs to develop a new design. In a product design, packaging use is as a wrapper and a promotional materials to attract customers. Therefore, the need for designing is accordance with the taste and desires of the customer’s psychological. Kansei Engineering approach is used to translating the customer feelings and impressions into the design parameters. The consumer criteria are identified by paper-based survey and validation test is used to test the hypothesis. Supported by the test, result of this study are able to produce packaging that satisfy the customer’s psychological desires.